Bimbingan Agama Terhadap Tindak Kriminal - Khahar, Abdul (Tasamuh: Jurnal Studi Islam, 2020)
The gap between religious norms or teachings and daily behavior is a sign of a multidimensional crisis. One impact is the increasingly widespread crime that occurred in the midst of society, both successfully covered by print and electronic media or other unpublished crimes. Crime is not a hereditary event (inherited from birth, inheritance), nor is biologically inherited. Criminal behavior that can be done by women or men, can take place at any age of children, adults or elderly. Crimes can be committed consciously that is fully considered, planned and directed at one specific purpose in a truly conscious manner. Also, it can be done semi-consciously, for example driven by intense impulses, wracked by very strong coercive impulses (compulsions), and by strong obsessions. Crimes can be done unconsciously at all, for example forced to defend his life, someone must react fighting even forced to strike back. Modern societies with middle to upper economic levels often foster high material aspirations and are often accompanied by unhealthy social ambitions.